Process, Integration, and Impact of Digital Public Service Policy Innovation on Public Sector Organizations (Faculty of Social Science, Universitas Negeri Semarang, 2022)
This study aims to discuss the innovation of digital public service policies based on the process, integration, and impact on public sector organizations, namely village governments. The research locus was Kubang Jaya Village, Serang Regency. This research applied a qualitative case study approach. Data collection technique was interviews with eight informants consisting of units in village government officials and the community. Data analysis was carried out by proposing patterns, categories, and themes from the bottom up (inductive). The results point out that digital public service policy innovations in Kubang Jaya Village Government have been running quite effectively, especially in service policy innovation that is proven to have specific impacts. However, in the context of its integration, it is still not fully effective due to the community's inadequate response in accepting service changes, the low level of education, and the lack of public knowledge about technology. These findings encourage higher public participation in committing digital service innovations and adaptive policy to respond to citizens' low digital literacy.